Economic Loss Due To Mental Fragility in The Analysis of Provincial Economic Productivity in Indonesia - Muhammad Taqwa; Etty Soesilowati; Imam Mukhlis (Economics and Business Journal (ECBIS), 2026)
Mental health is a strategic issue in economics because it affects the quality of human resources and regional economic productivity. This study aims to analyze the impact of schizophrenia, depression, and suicidal ideation on economic losses across provinces in Indonesia and to examine the role of depression treatment as a mediating variable. The study employs a quantitative approach using explanatory research and a cross-sectional design based on secondary data from 2023. Data were obtained from the Indonesian Health Survey (SKI) by the Ministry of Health of the Republic of Indonesia and Regional Gross Domestic Product (PDRB) data from the Central Statistics Agency, with 38 provinces in Indonesia as the units of analysis. Data analysis was conducted using descriptive statistics, multiple linear regression, and causal mediation analysis. The results of the study indicate that schizophrenia, depression, and suicidal ideation have a significant negative effect on economic loss, as proxied by per capita GRDP. Depression is the variable with the greatest negative impact on regional economic productivity. Furthermore, treatment for depression was found to act as a significant mediator capable of mitigating the negative impact of depression on economic loss. These findings indicate that improved access to mental health services contributes to increased community economic productivity and a reduction in regional economic losses. This study makes a theoretical contribution to the development of development economics and health economics research through the integration of mental health variables and regional economic productivity. Practically, the research results underscore the importance of integrating mental health services into regional development policies to improve the quality of human resources and reduce economic loss in Indonesia.